PENGARUH STRUKTUR MODAL, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Widiya Anggraini; Ruswan Nurmadi; Azwansyah Habibie (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
The ipurpose iof ithis istudy iwas ito iexamine iand ianalyze ithe ieffect iof icapital istructure, iprofitability, ifirm igrowth ion ifirm ivalue iwith idevidend ipolicy ias ian iintervening ivariable. iThe iapproach iused iin ithis iresearch iis ia iquantitative iapproach. iThe ipopulation iin ithis istudy iare iall imanufacturing icompanies ilisted ion ithe iIndonesia iStock iExchange. iThe isample iin ithis istudy iused ipurposive isampling itotaling i21 icompanies. iData icollection itechniques iin ithis istudy iusing idocumentation itechniques. iThe idata ianalysis itechnique iin ithis istudy iused iStructural iLeast iSquare iusing istatistical ianalysis iusing ithe iAuter iModel iAnalysis itest, iInner iModel iAnalysis, iand iHypothesis iTesting. iData iprocessing iin ithis istudy iusing ithe iPLS i(Partial iLeast iSquare) isoftware iprogram. iThe iresults iof ithis istudy iprove ithat idirectly idebt ito iequity iratio, ireturn ion iassets ihave ian ieffect ion ifirm ivalue, igrowth iopportunity, idevidend ipayout iratio ihas ino ieffect ion ifirm ivalue, idebt ito iequity iratio ihas ino ieffect ion idevidend ipayout iratio, ireturn ion iassets, igrowth iopportunity ihas ian ieffect ito ithe idevidend ipayout iratio. iIndirectly, ithe idevidend ipayout iratio iis inot iable ito imediate ithe ieffect iof idebt ito iequity iratio, ireturn ion iassets iand igrowth iopportunity ion ifirm ivalue